Class Warrior The Selected Works of E. T. Kingsley - Kingsley, E. T. (Athabasca University Press, 2022)
In October 1890, Eugene T. Kingsley's life changed irrevocably when he was injured in a fall between two rail cars while working as a brakeman on the Northern Pacific Railway. Following the amputation of both his legs, Kingsley became radicalized and joined the Socialist Labor Party in San Francisco. His activism eventually brought him to Vancouver, B.C. where he founded the Socialist Party of Canada. A self-described "uncompromising enemy of class rule and class robbery," Kingsley wrote prolifically on the exploitation of wage slaves by the capitalist class. Also known as a passionate orator, he went on to become one of the most prominent socialist intellectuals of his day. Class Warrior is a collection of Kingsley's writing and speeches that underscores his tremendous impact on Canadian political discourse.